Genetic diagnosis of congenital hypopituitarism by a target gene panel: novel pathogenic variants in GLI2, OTX2 and GHRHR. Issue 5 (May 2019) - Nakaguma, Marilena; Correa, Fernanda A; Santana, Lucas S; Benedetti, Anna F F; Perez, Ricardo V; Huayllas, Martha K P; Miras, Mirta B; Funari, Mariana F A; Lerario, Antonio M; Mendonca, Berenice B; Carvalho, Luciani R S; Jorge, Alexander A L; et al.
Abstract : Aim: Congenital hypopituitarism has an incidence of 1:3500–10, 000 births and is defined by the impaired production of pituitary hormones. Early diagnosis has an impact on management and genetic counselling. The clinical and genetic heterogeneity of hypopituitarism poses difficulties to select the order of genes to analyse. The objective of our study is to screen hypopituitarism genes (candidate and previously related genes) simultaneously using a target gene panel in patients with congenital hypopituitarism. Methods: Screening of 117 subjects with congenital hypopituitarism for pathogenic variants in 26 genes associated with congenital hypopituitarism by massively parallel sequencing using a customized target gene panel. Results: We found three novel pathogenic variants in OTX2 c.295C>T:p.Gln99*, GLI2 c.1681G>T:p.Glu561* and GHRHR c.820_821insC:p.Asp274Alafs*113, and the previously reported variants in GHRHR c.57+1G>A and PROP1 [c.301_302delAG];[c.109+1G>A]. Conclusions: Our results indicate that a custom-designed panel is an efficient method to screen simultaneously variants of biological and clinical relevance for congenital GH deficiency. A genetic diagnosis was possible in 5 out of 117 (4%) patients of our cohort. We identified three novel pathogenic variants in GHRHR, OTX2 and GLI2 expanding the spectrum of variants associated with congenital hypopituitarism.